SÀNG LỌC CÁC CHỦNG KHÁNG NẤM GÂY BỆNH THỰC VẬT VÀ MÔ TẢ CHI TIẾT CHỦNG Streptomyces hydrogenans VTCC 41117 CÓ HOẠT TÍNH CAO - Lưu, Trần Đông; Vũ, Sơn Tùng; Nguyễn, Thị Vân; Đinh, Thị Ngọc Mai; Nguyễn, Hồng Minh; Nguyễn, Công Nữ Thảo (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SCREENING FOR ANTAGONISTIC ACTINOMYCETES AGAINST FIVE PLANT PATHOGENIC FUNGI AND DESCRIPTION OF THE STRONG ACTIVITY STRAIN Streptomyces hydrogenans VTCC 41117Diseases caused by fungi are a huge threat to agricultural production. Currently more than 8 000 species of fungi are known to cause plant diseases, greater than any other pathogen. Among them, there are 05 common fungal pathogens causing diseases on thousands of different plant species including Phytophthora capsici, Alternaria sp., Colletotrichum gloeosporioides, Fusarium sp. and Botrytis cinerea. Biological control approach using actinomycetes to control fungal diseases on plants are considered very potential and safe for the environment. However, for this method to be highly effective, it is necessary to have strains with strong antifungal activities. In this study, 245 actinomycete strains preserved at the Vietnam Type Culture Collection (VTCC) were screened for its antagonistic activity against 5 strains of fungal pathogens. The screening results showed that strain VTCC 41117 had a strong and stable antagonistic activity against all 5 strains Alternaria sp., Botrytis cinerea, Colletotrichum gloeosporioides, Phytophthora capsici and Fusarium sp. with inhibitory effect of 40-55%. Results of identification by 16S rDNA sequence showed that VTCC 41117 strain is Streptomyces hydrogenans. Physiological, biochemical properties, cultivation conditions of VTCC 41117 were also identified in this study.